Analysis of the Impact of Financial Literacy and Banking Inclusion on Household Consumption Inequality in the Digitalization Era - Indri Yuliafitri; Wedia Hastuti (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2026)
This research addresses the "digital finance paradox" in Indonesia, where rapid financial technology adoption often outpaces cognitive readiness, potentially exacerbating consumption inequality. This study investigates the impact of financial literacy and digital banking inclusion on the consumption Gini Ratio across 38 provinces. Utilizing secondary panel data from the 2024 National Survey of Financial Literacy and Inclusion (SNLIK) by OJK and the 2024-2025 Susenas by BPS, the analysis encompasses a national sample of approximately 15,000 individuals and 345,000 households. An econometric model using panel data regression was applied to evaluate how literacy moderates the relationship between digital access and expenditure distribution. Results indicate that while digital inclusion has expanded significantly, its ability to reduce inequality is strictly contingent upon financial literacy, which exerts a significantly higher impact coefficient () than isolated access. High inclusion in low literacy regions correlates with increased non productive debt and higher Gini Ratios, whereas urban areas leverage a "digital dividend" to lower consumption costs. These findings imply that current policies over prioritize account ownership at the expense of user empowerment. The study concludes that the Indonesian government must reorient its National Strategy (SNLKI) toward "usage quality" and digital consumer protection to prevent systemic segregation. Future research should explore the role of digital trust and central bank digital currencies in further stabilizing household welfare.